2018
DOI: 10.1093/cje/bey027
|View full text |Cite
|
Sign up to set email alerts
|

Internal devaluation in a wage-led economy: the case of Spain

Abstract: El ICEI no comparte necesariamente las opiniones expresadas en este trabajo, que son de exclusiva responsabilidad de sus autores. The aim of this paper is to use the theoretical distinction between wage-led and profit-led economies to consider the impact of internal devaluation policy on GDP growth for the case of Spain. We assess to what extent wage devaluation in Spain has proven useful vis-à-vis triggering an exportled strategy, boosting aggregate demand and overcoming the crisis. For said purpose, we estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…How the demand for employment changes when wages change requires assessing the overall effect of a change in income distribution on investment, consumption and net exports. As already mentioned, empirical studies based on the Bhaduri-Marglin model find that Spain is a wage-led economy (Naastepad and Storm, 2007;Onaran and Obst, 2016;Álvarez et al, 2018): reductions in the wage share tend to detract potential growth from the economy, since the positive effect of lower labor costs on net exports fails to offset weaker domestic demand.…”
Section: Appendix 1 Data and Alternative Estimationsmentioning
confidence: 98%
See 1 more Smart Citation
“…How the demand for employment changes when wages change requires assessing the overall effect of a change in income distribution on investment, consumption and net exports. As already mentioned, empirical studies based on the Bhaduri-Marglin model find that Spain is a wage-led economy (Naastepad and Storm, 2007;Onaran and Obst, 2016;Álvarez et al, 2018): reductions in the wage share tend to detract potential growth from the economy, since the positive effect of lower labor costs on net exports fails to offset weaker domestic demand.…”
Section: Appendix 1 Data and Alternative Estimationsmentioning
confidence: 98%
“…Although, in theory, the net effect of a wage reduction on aggregate demand is theoretically undetermined -two influences pulling in opposite directions confront each other-there is empirical evidence to show that Spain is a wage-led economy (Naastepad and Storm, 2007;Onaran and Obst, 2016;Álvarez et al, 2018). That is to say, a reduction in the wage share -like the one caused by the wage devaluation strategy over the last decade-has negative effects on economic growth.…”
Section: 2-an Alternative Explanation Of the Spanish Recovery Basedmentioning
confidence: 99%
“…In order to calculate these effects, we follow a single-equation methodology as it reflects the contribution of each aggregate demand component to GDP growth, whereas simultaneous equation models are more suitable for considering exogenous shocks. This methodology is largely found in the literature (Álvarez et al, 2018;Onaran and Obst, 2016;Storm and Naastepad, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such practices were enhanced by the wage‐devaluation policy in place since 2010 (Álvarez et al . 2019). Additionally, labour relations literature has revealed that the capability of collective bargaining to reduce labour segmentation is decreasing as a consequence of decentralization policy (Muñoz de Bustillo and Pinto 2018).…”
Section: Discussionmentioning
confidence: 99%